Hominis Placenta facilitates hair re-growth by upregulating cellular proliferation and expression of fibroblast growth factor-7. Issue 1 (December 2016) - Seo, Hyung-Sik; Lee, Dong-Jin; Chung, Jae-ho; Lee, Chang-Hyun; Kim, Ha; Kim, Jae; Kim, Byung; Jung, Myeong; Ha, Ki-Tae; Jeong, Han-Sol
Abstract Background Hominis Placenta (HP) known as a restorative medicine in Traditional Chinese Medicine (TCM), has been widely applied in the clinics of Korea and China as an anti-aging agent to enhance the regeneration of tissue. This study was conducted to investigate whether topical treatment of HP promotes hair regrowth in the animal model. Methods The dorsal hairs of 8-week-old C57BL/6 mice were depilated to synchronize hair follicles to the anagen phase. HP was applied topically once a day for 15 days. Hair growth was evaluated visually and microscopically. The incorporation of bromodeoxyuridine (BrdU) and expression of proliferating cell nuclear antigen (PCNA), fibroblast growth factor-7 (FGF-7) in dorsal skin tissue was examined by immunohistochemical analysis. Reverse transcription polymerase chain reaction (RT-PCR) was used to measure the mRNA expression of FGF-7. Results HP exhibited potent hair growth-promoting activity in C57BL/6 mice. Gross examination indicated that HP markedly increased hair regrowth as well as hair density and diameter. Histologic analysis showed that HP treatment enhanced the anagen induction of hair follicles. Immunohistochemical analysis revealed that BrdU incorporation and the expressions of PCNA were increased by treatment of HP. HP treatment significantly increased the expression of FGF-7, which plays pivotal roles to maintain anagen phase both protein and mRNA levels. Conclusions Taken together, our results indicate that HP has a potent hair growth-promoting activity; therefore, it may be a good candidate for the treatment of alopecia.